Rescue archaeology heritage valuation in Europe’s largest dam – Alqueva: ex-situ products as elements of creative tourism - Dias-Sardinha, I. (2015)
The study aims to determine how the knowledge obtained from the study of prehistoric heritage found during the construction of the Alqueva dam and irrigation system (Portugal) can enhance the current tourist experience of the destination. A new approach is necessary given the inaccessibility of the archaeological remains, thus creative tourism and experience economy frame the theoretical basis of this paper. Semi?directed interviews were carried out to 35 tourism stakeholders in order to assess their view of the regional tourism experience, their interest in ex?situ and virtual products based on the archaeological knowledge and how these may add to the Alqueva destination. Findings show that stakeholders are still firmly attached to the conventional approach to archaeology but that, even though unaware of the archaeological findings, they believe that they could benefit from the introduction of creative products as a way of complementing the current offer.